An Investigation into Knowledge of the Concept of Consumption: A Case of BA Students - Babayigit, Mehmet Veysi; Cizrelioğulları, Mehmet Necati; Altun, Özlem (My University, 2021)
Consumption has changed considerably since the second half of the 20th century; in fact, it has become one of the social concepts. As the concept of consumption garners attention, and intensity, psychological, social, economic, cultural, and structural factors have come to significantly affect individual consumption habits. This research aims to investigate the effects of knowledge of consumption patterns on the consumption habits of students in the departments of Kurdish Language and Culture and English Language Education at Dicle University. A quantitative method using a questionnaire was applied to 130 of the 180 students enrolled in these departments. Descriptive, factor, t-test, and regression analyses were performed using SPSS Statistics 22. The findings reveal that the students were on the idea that there is a correlation between their knowledge with regard to gender, family income level, and employment status of consumption behavior. Additionally, environmental factors that determine consumption habits positively affect the consumption behavior of the students and social media. There is a serious lack of studies on this subject; this study will hopefully inspire future work on this topic.
Keywords: İktisat; Dil ve Dil Bilim